Identifying and Debunking Environmentally-Related False News Stories - An Experimental Investigation - Sven Grun̈er (German Journal of Agricultural Economics (GJAE), 2021)
The vast majority of studies in the realm of false information are currently conducted in the realm of political topics and Covid-19. This study addresses environmentally-related news stories. With the help of two experiments, I explore determinants that can explain who is good at distinguishing between accurate (i.e., factually correct) and false information and compare several intervention scenarios to debunk false information. In experiment one, subjects had to rate environmentally-related news stories as accurate or false. Afterward, subjects received systematically varied information about the correctness of the news stories depending on the experimental condition they had been randomly assigned to. After a period of three weeks, the subjects were asked to evaluate the news stories again (experiment two). In experiment one, I find that the perceived familiarity with news stories increased the propensity to accept them as true. Moreover, actively open-minded thinking helped to distinguish between accurate and false information. But the willingness to think deliberately did not seem to be important. In experiment two, it can be found that by repeating false news stories, subjects were more likely to adequately identify them later (i.e., no evidence for a familiarity backfire effect). However, it decreased the likelihood to adequately identify accurate news stories. A somewhat reverse, but weaker effect occurred when factually correct news stories were repeated: the correct identification of accurate news stories was more successful, but the opposite holds for the identification of false news stories.
Keywords: 330; false news information; narratives; cognitive reflection test; actively open-minded thinking; environmental economics